Field Trial on Overdosed Organic Manures on Chemical Properties of Soil - Senthil Murugan, A. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT In this present study, the field experiment was conducted to evaluate the overdosed effect of organic manures on chemical properties of soil under potato cultivation field. The experimental plot was divided into 15 sub-plots with size of 5m x 5m of which 5 sub-plots each allotted for compost, vermicompost and vermileachate treatment and one sub-plot of vermileachate was kept as control. Compost and vermicompost were applied with increasing concentration of 10 tonne/ha to 60 tonne/ha in the interval of 10 tonne/ha of potato field. Vermileachate was prepared at different dilution of water via 25%, 50%, 75% and 100% (v/v) and irrigated at the rate of 3L/5sq.m at 15days interval. At the end of experiment, chemical properties viz., pH, EC, organic carbon and available N, P and K of post-manure soils were estimated. As the application of organic manures increases carbon level in the soil, it improves the soil fertility as well as offset CO2 level from atmosphere.